(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Stress-related functional disturbances of the autonomic nervous system are increasingly observed in young adult populations, often without clear clinical manifestations. At early stages, these disturbances primarily affect regulatory mechanisms rather than structural or biochemical parameters. Heart rate variability reflects the dynamic balance between sympathetic and parasympathetic influences and provides a sensitive biophysical marker of autonomic regulation under stress conditions.